2016
DOI: 10.1177/0264619616651301
|View full text |Cite
|
Sign up to set email alerts
|

Communication and language profiles of children with congenital deafblindness

Abstract: To be born deaf and blind creates both communicative and language acquisition barriers for a child. Although case studies, research, and practical reports have described the severe communicative delay that children with congenital deafblindness (CDB) often experience, to date, no population studies have given a systematic overview of the characteristics of communication, language use, and language acquisition. This study investigates modes of communication and level of language acquisition among 71 children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
1
21
0
2
Order By: Relevance
“…Studies on the needs of families with a child with deafblindness have shown that intensive support is needed for both the child and his or her family members (see Correa-Torres & Bowen, 2016, for a review). Dammeyer and Ask Larsen (2016) reported in this journal that there appears to be a lack of individual language support for people with congenital deafblindness by their social partners.…”
Section: The Challenge Of Identifying Deafblindnessmentioning
confidence: 99%
“…Studies on the needs of families with a child with deafblindness have shown that intensive support is needed for both the child and his or her family members (see Correa-Torres & Bowen, 2016, for a review). Dammeyer and Ask Larsen (2016) reported in this journal that there appears to be a lack of individual language support for people with congenital deafblindness by their social partners.…”
Section: The Challenge Of Identifying Deafblindnessmentioning
confidence: 99%
“…While some of the deafblind people are born with this condition, a majority of them acquire deaf blindness at later stage in their life and therefore they are likely to have learnt some language (English, for instance) [1]. A number of deafblind people in this category generally use the English block letters to communicate [5]. The English block letter is a tactile deafblind communication method in which the deafblind person brings out the palm and the sender writes letters on it to communicate ( Fig.…”
Section: Deafblind Communication -State Of the Artmentioning
confidence: 99%
“…1. The method involves deafblind person writing the English block letters with their finger on to the palm of the receiving person [5]. Here, the haptic feedback substitutes the impaired vision and auditory sensory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The deaf blind child is not exposed in visual information gained from the body language and the facial expressions. [9,10,11,12]Additionally, the child does not perceive and experience the auditory stimulation from the parents' voice intonation. Moreover the self-awareness, selfconcept development and body awareness, often, may only be perceived during structured locomotion activities and through tactile stimulation and exploration.…”
Section: The Deaf-blind Population: Social and Emotional Development mentioning
confidence: 99%